Using item analysis on essay types questions given in summative examination of medical college students: facility value, discrimination index - Khan, Gul-Ar Navi; Ishrat, Nazia; Khan, Abdul Qayyum (International Journal of Research in Medical Sciences, 2017)
Background:The most common tool used for assessment of knowledge is the essay questions. Their evaluations depend upon test and item analysis which is consisting of analysis of individual questions and analysis of the whole test. The objective of our study was to calculate the Item analysis (Facility value, FV and discrimination index, DI) of questions given in terminal examination of MBBS students and observes the adequacy of questions framing in examination. Methods:Study contains 150 medical students undergone terminal examination consist of questions of essay type, structured essay type and short answer questions were given to the students. We divide them into high ability group and low ability group. Mark range was decided for essay type, structured essay type and short answer type questions and FV & DI was calculated. Results:Studies described that facility values of 62.5 percentage questions were come under recommended & acceptable range and 50 percentage questions were come under acceptable range. Discrimination value of 100 percentage questions were come under recommended & acceptable range where 75 percentage questions were come under acceptable range. Conclusion:The importance of item analysis is highlighted from our results. For improvement of examination items with average difficulty and high discrimination should be implemented into future examinations to improve test scores and properly discriminate among the students.